Institutions and the economy - Duina, Francesco G., 1969- (Economy and society series (Cambridge, England), 2011)
Institutions are central to economic life. They have a major impact on consumer preferences, the actions and processes of firms, levels of wealth and poverty in countries, the growth of international trade, and much more. Indeed, none of the preconditions for economic activity - such as the existence of buyers and sellers, recognizable goods and services, and the information we need to make choices - would be in place without institutions. Institutions, then, do more than support economic life: they enable and shape it. These insights challenge some of the most basic postulates on modern economic theory and are at the heart of many of the most exciting works in economic sociology. This book examines the role of institutions - defined as the formal and informal rules and practices that surround us as we go about our daily lives - in the economy. Illuminating complex ideas with carefully selected, vivid examples, the investigation focuses on economic activity as it unfolds at the individual, organizational, national, and international levels. This accessible and engaging book will be essential reading for students of economic sociology, and all those interested in the intimate relationship between institutions and the economy. -- Book Description.